Study on the interactions between melamine-cored Schiff bases with cucurbit[n]urils of different sizes and its application in detecting silver ions - Gou, Jun-Xian; Luo, Yang; Yang, Xi-Nan; Zhang, Wei; Lu, Ji-Hong; Tao, Zhu; Xiao, Xin (Beilstein Journal of Organic Chemistry, 2021)
Three different complexes, TMeQ[6]-TBT, Q[7]-TBT, and Q[8]-TBT are constructed by three different cucurbiturils and synthesized by guest melamine-cored Schiff bases (TBT) through outer-surface interaction and host–guest interactions. TBT forms a TMeQ[6]-TBT complex with TMeQ[6] through outer-surface interaction, while Q[7]-TBT and Q[8]-TBT form complexes with Q[7,8] through host–guest interactions. Among them, Q[7]-TBT is selected as a UV detector for the detection of silver ions (Ag+). This work makes full use of the characteristics of each cucurbituril and melamine-cored Schiff base to construct a series of complexes and these are applied to metal detection.
Keywords: cucurbiturils; melamine; Schiff base; silver ion

(untitled) - Schiff, H. (Justus Liebigs Ann. Chem., 1864)

(untitled) - Jia, Y.; Li, J. (Chem. Rev., 2015)

(untitled) - Rezaeivala, M.; Keypour, H. (Coord. Chem. Rev., 2014)

(untitled) - Horak, E.; Vianello, R.; Hranjec, M.; Murković Steinberg, I. (Supramol. Chem., 2018)

(untitled) - Nastasă, C.; Vodnar, D. C.; Ionuţ, I.; Stana, A.; Benedec, D.; Tamaian, R.; Oniga, O.; Tiperciuc, B. (Int. J. Mol. Sci., 2018)

(untitled) - Gupta, K. C.; Sutar, A. K. (Coord. Chem. Rev., 2008)

(untitled) - Aluthge, D. C.; Patrick, B. O.; Mehrkhodavandi, P. (Chem. Commun., 2013)

(untitled) - Okuhata, M.; Funasako, Y.; Takahashi, K.; Mochida, T. (Chem. Commun., 2013)

(untitled) - Seo, M.-S.; Kim, K.; Kim, H. (Chem. Commun., 2013)

(untitled) - Fu, S.; Liu, Y.; Ding, Y.; Du, X.; Song, F.; Xiang, R.; Ma, B. (Chem. Commun., 2014)

(untitled) - Matsunaga, S.; Shibasaki, M. (Chem. Commun., 2014)

(untitled) - Wang, T.; Douglass, E. F., Jr; Fitzgerald, K. J.; Spiegel, D. A. (J. Am. Chem. Soc., 2013)

(untitled) - Wang, J.; Yan, B. (Anal. Chem. (Washington, DC, U. S.), 2019)

(untitled) - Bruemmer, K. J.; Walvoord, R. R.; Brewer, T. F.; Burgos-Barragan, G.; Wit, N.; Pontel, L. B.; Patel, K. J.; Chang, C. J. (J. Am. Chem. Soc., 2017)

(untitled) - Schwab, M. G.; Fassbender, B.; Spiess, H. W.; Thomas, A.; Feng, X.; Müllen, K. (J. Am. Chem. Soc., 2009)

(untitled) - Freeman, W. A.; Mock, W. L.; Shih, N. Y. (J. Am. Chem. Soc., 1981)

(untitled) - Lee, J. W.; Samal, S.; Selvapalam, N.; Kim, H.-J.; Kim, K. (Acc. Chem. Res., 2003)

(untitled) - Liu, S.; Zavalij, P. Y.; Isaacs, L. (J. Am. Chem. Soc., 2005)

(untitled) - Yang, X.; Liu, F.; Zhao, Z.; Liang, F.; Zhang, H.; Liu, S. (Chin. Chem. Lett., 2018)

(untitled) - Yu, G.; Jie, K.; Huang, F. (Chem. Rev., 2015)

(untitled) - Ni, X.-L.; Xiao, X.; Cong, H.; Zhu, Q.-J.; Xue, S.-F.; Tao, Z. (Acc. Chem. Res., 2014)

(untitled) - Huang, Y.; Gao, R.-H.; Liu, M.; Chen, L.-X.; Ni, X.-L.; Xiao, X.; Cong, H.; Zhu, Q.-J.; Chen, K.; Tao, Z. (Angew. Chem., Int. Ed., 2021)

(untitled) - Liu, M.; Chen, L.; Shan, P.; lian, C.; Zhang, Z.; Zhang, Y.; Tao, Z.; Xiao, X. (ACS Appl. Mater. Interfaces, 2021)

(untitled) - Yang, D.; Liu, M.; Xiao, X.; Tao, Z.; Redshaw, C. (Coord. Chem. Rev., 2021)

(untitled) - Uysal, Ş.; Koç, Z. E. (J. Hazard. Mater., 2010)

(untitled) - Kataki-Anastasakou, A.; Axtell, J. C.; Hernandez, S.; Dziedzic, R. M.; Balaich, G. J.; Rheingold, A. L.; Spokoyny, A. M.; Sletten, E. M. (J. Am. Chem. Soc., 2020)

(untitled) - Wu, H.; Wang, Y.; Jones, L. O.; Liu, W.; Song, B.; Cui, Y.; Cai, K.; Zhang, L.; Shen, D.; Chen, X.-Y.; Jiao, Y.; Stern, C. L.; et al. (J. Am. Chem. Soc., 2020)

(untitled) - Huang, Z.; Chen, X.; Wu, G.; Metrangolo, P.; Whitaker, D.; McCune, J. A.; Scherman, O. A. (J. Am. Chem. Soc., 2020)

(untitled) - Meng, Y.; Zhao, W.; Zheng, J.; Jiang, D.; Gao, J.; Jin, Y.; Ma, P. (RSC Adv., 2021)

(untitled) - Li, S.; Xia, W.; Zhang, Y.; Tao, Z. (New J. Chem., 2020)

(untitled) - Xu, W.; Deng, X.; Xiao, X.; Bian, B.; Chen, Q.; Dalgarno, S. J.; Tao, Z.; Redshaw, C. (New J. Chem., 2020)

(untitled) - Geng, Q.-X.; Wang, F.; Cong, H.; Tao, Z.; Wei, G. (Org. Biomol. Chem., 2016)

(untitled) - Zhang, W.; Luo, Y.; Zhou, Y.; Liu, M.; Xu, W.; Bian, B.; Tao, Z.; Xiao, X. (Dyes Pigm., 2020)

(untitled) - Koç, Z. E.; Uysal, Ş. (Helv. Chim. Acta, 2010)